Eu-doped ZnO quantum dots with solid-state fluorescence and dual emission for high-performance luminescent solar concentrators. (6th May 2021) - Gong, Xiao; Jiang, Hang; Cao, Mengyan; Rao, Zhihui; Zhao, Xiujian; Vomiero, Alberto
Abstract : Eu-doped ZnO quantum dots with strong solid-state fluorescence and dual emission are synthesized via a simple sol–gel method, which can be used for fabrication of high-performance luminescent solar concentrators. Abstract : Heavy-metal-free quantum dots (QDs) are promising luminophores for luminescent solar concentrators (LSCs) because of environmental friendliness, which is essential for industrial applications. In order to keep high optical quality and inhibit aggregation-induced quenching, usually QDs can only be loaded at low concentration in a polymer optical waveguide material for LSCs, which significantly impairs the power conversion efficiency (PCE). Thus, it is a challenge to fabricate high-performance LSCs with high QD loading. Here, dual emission Eu-doped ZnO QDs with strong solid-state fluorescence are synthesized via a simple sol–gel method, which enables two characteristic photoluminescence peaks at 551 nm and 614 nm. Furthermore, Eu-doped ZnO QDs with dual fluorescence emission are for the first time reported to be applied in LSCs. The performance of LSCs can be influenced by the loading concentration of Eu-doped ZnO QDs in polyvinyl pyrrolidone (PVP) films. The obtained external optical efficiency ( η opt ) of the LSCs based on Eu-doped ZnO QDs can be relatively high (4.37%) compared to the reported LSCs with a similar area when the loading concentration of Eu-doped ZnO QDs is up to 13.2% because of both their high photoluminescence intensity and dual fluorescence emission. Our results demonstrate that dual emission Eu-doped ZnO QDs with strong solid-state fluorescence are promising candidates as luminophores for LSCs.